Performance Improvement of Kötter and Kschischang Codes and Lifted Rank Metric Codes in Random Linear Network Coding - Guefrachi, Aicha; Nighaoui, Sarra; Zaibi, Sonia; Bouallegue, Ammar (Mobile networks and applications, 2023)
Future networks require low latency communications which can be achieved using Network Coding. While random linear network coding is an effective technique for disseminating information in networks, it is highly sensitive to error propagation. Classical error correction codes are therefore inadequate to solve the problem, which requires new techniques. Recently, Kötter and Kschischang (KK) codes, have been proposed for error control in non-coherent random linear network coding. These codes can also be constructed from the lifting of rank metric codes (LRMC) as Gabidulin codes. In this paper, we first propose a novel coding scheme in mesh networks to improve the performance of KK and LRMC codes in random linear network coding, using cyclic redundancy check (CRC) codes to prevent error propagation. Then, we give a performance evaluation and comparison between KK and LRMC codes in terms of Packet Error Rate (PER) without and with error detection. Simulation results show that a significant performance improvement in terms of PER is achieved using our proposed scheme.